2018
DOI: 10.3389/fphys.2018.00432
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Chemosensory Genes Based on the Transcriptomic Analysis of Six Different Chemosensory Organs in Spodoptera exigua

Abstract: Insects have a complex chemosensory system that accurately perceives external chemicals and plays a pivotal role in many insect life activities. Thus, the study of the chemosensory mechanism has become an important research topic in entomology. Spodoptera exigua Hübner (Lepidoptera: Noctuidae) is a major agricultural polyphagous pest that causes significant agricultural economic losses worldwide. However, except for a few genes that have been discovered, its olfactory and gustatory mechanisms remain uncertain.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
20
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 100 publications
(131 reference statements)
3
20
1
Order By: Relevance
“…In the present study, we identified 45 ORs, 9 IRs, 8 GRs and 2 SNMPs from our previous H. rhodope transcriptomic data ( Yang et al, 2020 ). The number of chemoreceptor genes in H. rhodope was less compared to previously reported numbers in other nocturnal lepidopteran species, such as 62 ORs, 20 IRs and 16 GRs in Mythimna separata ( Du et al, 2018 ), 64 ORs, 22 IRs and 30 GRs in Spodoptera exigua ( Zhang et al, 2018 ), 60 ORs, 21 IRs and 197 GRs in H. armigera ( Liu et al, 2014 ; Xu et al, 2016 ), 60 ORs, 17 IRs and 17 GRs in S. littoralis ( Walker III et al, 2019 ) and 58 ORs, 21 IRs and 22 GRs in C. pomonella ( Walker III et al, 2016 ). Previous studies reported that different chemosensory behavior ( Zhang et al, 2017 ), life stage ( He et al, 2017 ), ecological niche breadth ( Gouin et al, 2017 ), phenotype ( Purandare & Brisson, 2020 ), mating status ( Jin et al, 2017 ), circadian rhythm ( Gadenne, Barrozo & Anton, 2016 ) and feeding trait ( Taparia, Ignell & Hill, 2017 ) influence the variation in chemosensory gene number.…”
Section: Discussioncontrasting
confidence: 69%
“…In the present study, we identified 45 ORs, 9 IRs, 8 GRs and 2 SNMPs from our previous H. rhodope transcriptomic data ( Yang et al, 2020 ). The number of chemoreceptor genes in H. rhodope was less compared to previously reported numbers in other nocturnal lepidopteran species, such as 62 ORs, 20 IRs and 16 GRs in Mythimna separata ( Du et al, 2018 ), 64 ORs, 22 IRs and 30 GRs in Spodoptera exigua ( Zhang et al, 2018 ), 60 ORs, 21 IRs and 197 GRs in H. armigera ( Liu et al, 2014 ; Xu et al, 2016 ), 60 ORs, 17 IRs and 17 GRs in S. littoralis ( Walker III et al, 2019 ) and 58 ORs, 21 IRs and 22 GRs in C. pomonella ( Walker III et al, 2016 ). Previous studies reported that different chemosensory behavior ( Zhang et al, 2017 ), life stage ( He et al, 2017 ), ecological niche breadth ( Gouin et al, 2017 ), phenotype ( Purandare & Brisson, 2020 ), mating status ( Jin et al, 2017 ), circadian rhythm ( Gadenne, Barrozo & Anton, 2016 ) and feeding trait ( Taparia, Ignell & Hill, 2017 ) influence the variation in chemosensory gene number.…”
Section: Discussioncontrasting
confidence: 69%
“…In contrast, the molecular and physiological mechanisms that underlie olfactory behaviours in larvae are poorly understood and only few reports have described the chemosensory gene set expressed at the larval stage (Chang et al, 2017;Di et al, 2017;McCormick et al, 2017;Poivet et al, 2013;Tanaka et al, 2009;Walker et al, 2016) compared to the plethora of adult transcriptomes available (Montagné et al, 2015). Here, we identified chemosensory-related genes expressed in S. exigua larval heads using RNA-seq and RT-PCR data, expanding previous datasets built from adult data (Du et al, 2018;Zhang et al, 2018). We also developed a method to analyse S.…”
Section: Discussionmentioning
confidence: 73%
“…( Supplementary Figure 4). Two of the transcripts described by Zhang et al (2018) (OBP25 and OBPN-3) were not identified in our transcriptome. Compared to Du et al (2018), our annotation missed 19 putative OBPs.…”
Section: Annotation Of Chemosensory-related Genesmentioning
confidence: 90%
See 2 more Smart Citations